Employment of Telemedicine in Nursing Homes: Clinical Requirement Analysis, System Development and First Test Results - Ohligs, Marian (Clin Interv Aging, 2020)
PURPOSE: Demographic change and lack of specialized workforces are challenging. Likewise, home visits by general practitioners (GPs) become rarer. If a nursing home resident develops acute symptoms, nurses are often inclined to call the rescue service. Besides patient-related consequences, this might lead to unnecessary hospitalization and far-reaching health economic costs. Due to legal restrictions of remote treatment in Germany, which were recently loosened, telemedicine is still in the early stages. The aim of this study was to employ a holistic telemedical system for nursing homes which facilitates the connection to a GP and thus avoids unnecessary hospitalizations in the case of ambulatory-sensitive illnesses. MATERIALS AND METHODS: After an inter-professional requirement analysis, the iterative development was started. In addition to an audio-video connection, several point of care measurements were integrated. Finally, first field tests were performed in a nursing home in a rural area in Germany. RESULTS: One nursing home was equipped with telemedical system based on the results of the requirement analysis and tele-medically connected to a GP. Over a period of seven months, 56 routine and emergency teleconsultations took place. Only one of those required a hospital admission. In addition to video telephony, electrocardiography and assessment of vitals such as pulse, blood pressure, oxygen saturation and auscultation of heart and lungs were applied frequently. CONCLUSION: A telemedical system including integrated medical devices was successfully developed and has turned out to be helpful and even necessary for careful and reliable decision-making by the GP. First test results show high acceptance for elderly care. Involved patients, nurses, and the GP itemize various specific benefits, including economic, personal, and altruistic issues. Another issue that the current COVID-19 crisis brought to light is lowering the risk of contagion; GPs can replace their home visits by using telepresence combined with point of care measures.